Bio-based aliphatic polyesters of 1,4-butanediol with different diacids: Effect of carbon chain lengths on mechanical properties and enzymatic hydrolysis - Shuning Liu; Xinru Cheng; Tingting Su; Zhanyong Wang (eXPRESS Polymer Letters, 2024)
Polybutylene succinate, polybutylene adipate, polybutylene suberate and their copolyesters were synthesized. The physical properties and biodegradability of these polyesters were controlled by adjusting the composition of carboxyl monomers. Compared with the homopolyesters, the addition of comonomer during polymerization resulted in the formation of copolyesters with lower melting temperatures and crystallinity. Among them, poly(butylene succinate-co-adipate) (PBSA) had the lowest crystallinity, and poly(butylene adipate-co-suberate) (PBASub) had the lowest melting point. The elongation at break and tensile strength of PBSA was 766.2% and 21.5 MPa, respectively. Enzymatic degradation by Fusarium solani cutinase (FsC) showed that both the crystalline and amorphous regions of the polyester were simultaneously degraded by FsC, and the crystal structure of the polyester was not disrupted. FsC preferentially got attached to the surface of polyesters, subsequently attacked the center of the films, and the water penetrated the amorphous region, leading to enhanced enzymatic hydrolysis. The biodegradability of copolyester was higher than that of homopolyesters. PBSA and poly(butylene succinate-co-suberate) (PBSSub) were completely degraded in about 10 h, and can be used in agricultural, automotive, electronics, biomedical materials, packaging, etc.